Pemikiran Pragmatisme Charles Sanders Peirce Dalam Pembelajaran Bermakna Di Sekolah Dasar - Indah Susi Irianti; Wahyu Aspri Nur Taryanti; Iim Fatimah; Endang Fauziati (Jurnal Kependidikan, 2025)
This study aims to analyse Charles Sanders Peirce's pragmatism in relation to meaningful learning, identify strategies for integrating this perspective into elementary school learning practices, and evaluate the improvement of student understanding through practical experiences informed by Peirce's perspective. The theoretical study examines Peirce's pragmatism as a philosophical foundation that emphasizes truth and knowledge acquired through practical and experimental experience, which aligns with meaningful learning that holistically connects subject matter with students' experiences. Deep learning is implemented to encourage in-depth analysis and critical application, while the integration of the two enables contextual and meaningful curriculum design within the context of the Independent Curriculum. The theoretical framework combines these elements to support the research objectives, providing a strong theoretical foundation for educational innovation and facilitating more effective and adaptive learning in support of national education reform.